Analisis Bibliometrik Return on Assets dan Firm Value Berbasis Data Scopus 2020–2025 - Siti Rahmatan; Muh. Irfandy Azis; Mohamad Nur Utomo; Irawati HM (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to map the development of literature on Return on Assets (ROA) and Firm Value during the period 2020–2025. ROA is considered a profitability indicator that reflects operational efficiency and serves as a signal for investors in assessing corporate prospects. The method employed is bibliometric analysis using VOSviewer software through a keyword co-occurrence approach based on Scopus data. The findings reveal a significant increase in publications, with ROA consistently occupying a central position in explaining Firm Value. Cluster analysis confirms that profitability, particularly ROA, is a fundamental node in the research ecosystem of corporate financial performance. These results strengthen the literature by emphasizing that Firm Value is inseparable from profitability, and ROA is the most relevant indicator to explain this relationship. This study contributes to the literature by highlighting the strong linkage between ROA and Firm Value across both developed and emerging markets. The practical implications suggest that companies should adopt ROA as a key reference in strategies to enhance firm value, while regulators are encouraged to improve financial reporting transparency to increase market trust in ROA.